Respuesta :
Answer:
(1, 9 )
Step-by-step explanation:
Given the 2 equations
y = x + 8 → (1)
y = 4x + 5 → (2)
Substitute y = 4x + 5 into (1)
4x + 5 = x + 8 ( subtract x from both sides )
3x + 5 = 8 ( subtract 5 from both sides )
3x = 3 ( divide both sides by 3 )
x = 1
Substitute x = 1 into either of the 2 equations for corresponding value of y
Substituting in (1)
y = 1 + 8 = 9
Solution is (1, 9 )
Answer:
X=1
Y=9
Step-by-step explanation:
y=x +8
y=4x +5
Collect like terms
y-x=8
y-4x=5
3x=3
Divide both sides by 3
x=1
Substitute x in equation (i)
y=x+8
y=1+8
y=9
: x=1
y=9